2003
DOI: 10.1073/pnas.2433350100
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the structure and dynamics of the human telomeric G quadruplex by single-molecule fluorescence resonance energy transfer

Abstract: We have investigated the structure and unfolding kinetics of the human telomeric intramolecular G quadruplex by using singlemolecule fluorescence resonance energy transfer. An exploration of conformational heterogeneity revealed two stable folded conformations, in both sodium-and potassium-containing buffers, with small differences between their enthalpies and entropies. Both folded conformations can be opened by the addition of a 21-base complementary DNA oligonucleotide. The unfolding of both substates occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
300
0
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 293 publications
(326 citation statements)
references
References 44 publications
21
300
0
5
Order By: Relevance
“…If the same is true for the unimolecular construct studied here, F 1 would correspond to the parallel conformation and F 2 to the antiparallel conformation. Circular dichroism measurements of the same DNA sequence and labeling also suggested that at room temperature and at 100 mM K ϩ the structure is mostly antiparallel (20), further supporting our assignment. Thus, our data suggest that the human telomeric DNA in physiological conditions (37°C, 140 mM K ϩ ) (28) is primarily folded with comparable populations of parallel and antiparallel conformations.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…If the same is true for the unimolecular construct studied here, F 1 would correspond to the parallel conformation and F 2 to the antiparallel conformation. Circular dichroism measurements of the same DNA sequence and labeling also suggested that at room temperature and at 100 mM K ϩ the structure is mostly antiparallel (20), further supporting our assignment. Thus, our data suggest that the human telomeric DNA in physiological conditions (37°C, 140 mM K ϩ ) (28) is primarily folded with comparable populations of parallel and antiparallel conformations.…”
Section: Resultssupporting
confidence: 80%
“…This observation also makes it very unlikely that F 1 and F 2 are different only in the dye properties. Even though fluorescent labeling does have some effects in that it slightly increased the stability of the G-quadruplex in 100 mM K ϩ (20), distinct conformations seen here are not likely to be caused by mere changes in dyes because interconversion between them requires G-quadruplex unfolding.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…[9][10][11][12][13][14] Fluorescence resonance electron transfer (FRET) in molecular beacons has been exploited in the detection of folded and unfolded states of oligonucleotides. [15][16][17] These changes have been coupled with sensing capabilities to detect a variety of analytes. FRET also has been used to detect movements of nanomachines.…”
Section: Introductionmentioning
confidence: 99%